Simulation of diffusion under pressure in bcc metals - Valikova, Irina V.; Nazarov, Andrei V. (Diffusion Fundamentals, 2005)
This work is devoted to simulation of atom configurations in bcc metals near the point defect using the molecular static method. The values of migration and formation volumes are very sensitive to the atomic structure in the vicinity of a defect, which makes it necessary to consider a large number of atoms in the computation cell and to take into account an elastic matrix around the cell. We have developed the new model taking into the consideration these factors. It allows to define “fine structure” of displacement atoms near the point defect. The atoms of third zone were embedded in an elastic continuum. The displacement of each atom embedded in an elastic continuum was defined as the first and the second terms in solution of elastic equation. In the framework of this model we calculated the formation and migration volumes of defect. Also we take into the consideration that the energy of system (in particular the system with defect) depends on the outer pressure. This dependence gives an addition to the values of migration and formation volumes.